Clowns and dragons! - Richard, Laurent, 1968- (Tao, the little samurai, 2014)
"Tao is a fearless samurai apprentice studying to become a virtuoso martial artist. But when you're naturally good at pranks, practical jokes, and other silly antics (including trying to teach kung fu moves to the big, lazy cat, Bruce Lee), it's hard to concentrate on learning how to slay dragons"--